2017
DOI: 10.24908/pceea.v0i0.6536
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Review on the Culture of Cheating in Undergraduate Engineering Programs

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Academic integrity in professional education has been a topic of particular interest among a select group of Canadian scholars who are concerned there may be a relationship between student breaches of integrity in school and misconduct or unethical behaviour in professional contexts after graduation. This topic has been explored in a variety of fields among Canadian scholars including education (Bens 2010), health sciences (Austin et al 2005(Austin et al , 2006Miron 2016) and engineering (Roncin 2013;Smith et al 2017).…”
Section: Academic Integrity In Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Academic integrity in professional education has been a topic of particular interest among a select group of Canadian scholars who are concerned there may be a relationship between student breaches of integrity in school and misconduct or unethical behaviour in professional contexts after graduation. This topic has been explored in a variety of fields among Canadian scholars including education (Bens 2010), health sciences (Austin et al 2005(Austin et al , 2006Miron 2016) and engineering (Roncin 2013;Smith et al 2017).…”
Section: Academic Integrity In Higher Educationmentioning
confidence: 99%
“…Little research has been conducted in Canada in this field (Smith et al 2017), but there are some notable exceptions. Hu (2001) used a qualitative case study to explore academic writing among 16 Chinese graduate students in sciences and engineering at the University of British Columbia Canada.…”
Section: Academic Integrity In Engineeringmentioning
confidence: 99%
“…Christensen Hughes and McCabe (2006a) identified that cheating may be a serious problem at post-secondary institutions in Canada and they called for further research into strategies that could be used to help improve academic integrity in our schools. Smith et al (2016) conducted an initial literature review on cheating in engineering schools, which was followed by Smith and Maw (2017) who completed a Canadian version of the P.A.C.E.S. study, which was originally developed by Carpenter et al (2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Smith et al [12], we reviewed the nature of academic dishonesty in North American (and primarily American) engineering programs, as it is currently understood in the literature. In [12], we noted that we had undertaken a parallel Canadian study utilizing the methods of Carpenter et al [2].…”
Section: Introductionmentioning
confidence: 99%
“…In [12], we noted that we had undertaken a parallel Canadian study utilizing the methods of Carpenter et al [2]. Our study employed a survey tool called CAIS-1 i.e.…”
Section: Introductionmentioning
confidence: 99%